Geochemical Constraints on the Hydrothermal Dolomitization of the Middle-Upper Cambrian Xixiangchi Formation in the Sichuan Basin, China - Liang, Jintong; Liu, Sibing; Li, Luping; Dai, Jie; Li, Xiaotian; Mou, Chuanlong (Frontiers in Earth Science, 2022)
The Middle-Upper Cambrian Xixiangchi carbonates in the Sichuan Basin have been pervasively dolomitized. In the presented work, petrographic investigation reveals three generations of the Xixiangchi dolomites, consisting of dolomicrite (D1, 5 to 20 μm) with planar-s to non-planar texture, fabric destructive dolomite (D2, 50 to 150 μm) with planar-s to planar-e texture, and saddle dolomite (D3, 300 μm to 4 mm) with planar-s to planar-e texture. D1 and D2 dolomites are presented as matrix dolomites, whereas D3 dolomites are observed as fracture-filling dolomites. Compared with the matrix D1 and D2 dolomites which are interpreted as products of dolomitization under-near surface or at shallow burial conditions, the depleted δ13C and δ18O values of D3 than D1 and D2 dolomites are probably caused by the temperature-controlled isotopic fractionation within an increasing fluid-rock interaction at burial. The enriched Mn, Sr, Ba concentrations of D3 than D1 and D2 dolomites suggest a newly introduced type of diagenetic fluids, which is probably related to the upwelling of magmatic activities (Emeishan Large Igneous Province). By contrast, the abnormally depleted Fe concentration in D3 dolomites is attributed to its preferential incorporation into other solid phases rather than its true concentration. The similar rare earth element (REE) partition patterns of D1 and D2 dolomites demonstrate similar dolomitization fluids related to seawater or marine-origin fluids. The hydrothermal-derived D3 dolomites exhibit a different REE partition pattern by contrast. The negative Eu anomalies of D3 dolomites may represent hydrothermal fluid cooling or association with intermediate-felsic igneous rocks. The findings of the presented work would enhance our understanding on the hydrothermal dolomitization of the Middle-Upper Cambrian Xixiangchi Formation.